2002
DOI: 10.1046/j.1471-4159.2002.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Albumin promotes neuronal survival by increasing the synthesis and release of glutamate

Abstract: It is well known that the presence of albumin within the brain and the CSF is developmentally regulated. However, the physiological relevance of this phenomenon is not well established. We have previously shown that albumin specifically increases the flux of glucose and lactate through the pyruvate dehydrogenase reaction in astrocytes. Here we show that, in neurones, albumin also increases the oxidation of glucose and lactate through the pyruvate dehydrogenasecatalysed reaction, the final purpose of this being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 62 publications
1
31
0
4
Order By: Relevance
“…Many Purkinje cells were also immunopositive for albumin. It has been shown that Purkinje cells are particularly prone to sequestering albumin [28] , which may be a protective response and an attempt to abrogate or forestall apoptosis [29] . Given that Purkinje cells form a population of cells that, after a certain time in development are not replaced, a deficit in these cells may result in significant life-long functional deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Many Purkinje cells were also immunopositive for albumin. It has been shown that Purkinje cells are particularly prone to sequestering albumin [28] , which may be a protective response and an attempt to abrogate or forestall apoptosis [29] . Given that Purkinje cells form a population of cells that, after a certain time in development are not replaced, a deficit in these cells may result in significant life-long functional deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in situ synthesis of albumin by neurons and blood-to-brain transfer of plasma proteins are processes present in the immature brain, these are not present in the fetal sheep brain after approximately 120 d gestation (40). Albumin uptake has been observed in cultured neurons, where it appears to influence glucose utilization, increase glutamate synthesis, and suppress apoptosis, suggesting that it promotes neuronal survival (41).…”
Section: Fetal Blood-brain Barrier and Endotoxinmentioning
confidence: 99%
“…Albumin's numerous functions include maintenance of colloid osmotic pressure (accounting for ϳ80%), buffering, and transport of bilirubin, uremic toxins, porphyrins, fatty acids, metals, cortisol, thyroxine, endotoxins, medications, and endogenous nitric oxide. Furthermore, it is thought to be an important antioxidant and as such could play a role in neuronal survival during development (42). These functions are of vital importance to the critically ill preterm neonate.…”
mentioning
confidence: 99%